Analysis of Floods in Xijiang River and Beijiang River Based on Copula Function - REN Chengjun (Renmin Zhujiang)
It is of great significance to analyze the flood situation of the Xijiang River and Beijiang River for peak shifting regulation of reservoirs in the basin and flood control and disaster reduction in the Pearl River Delta.Therefore,Gamma distribution and Von Mises distribution are used to fit the flood magnitude and occurrence time of annual maximum flood,respectively.The Copula function is used to construct a joint distribution of floods in Xijiang River and Beijiang River,and the possibility of floods in Xijiang River and Beijiang River is analyzed.The results show that the probability of simultaneous occurrence of major floods in Xijiang River and Beijiang River is extremely small.When Shijiao Station in Beijiang River experiences floods at a level of 5,10,20,50,100,and 200 a,respectively,the probability of occurrence of floods with the same frequency in Gaoyao Station Xijiang River is 0.345 0,0.200 3,0.108 5,0.046 6,0.023 7,and 0.012 0,respectively.The probability of floods in the two rivers is the highest in early June.As the flood magnitude increases,the risk of flood occurrence decreases.The probability of floods at a level of 5 a in the two rivers in early June is 1.32×10-3,and that of floods at a level of 200 a is only 1.17×10-6.